INTERNET SEARCH TRAFFIC AND ITS INFLUENCE ON LIQUIDITY AND RETURNS OF INDONESIA STOCKS: AN EMPIRICAL STUDY - Berto Usman; Eduardus Tandelilin (Faculty of Economics and Business, Universitas Gadjah Mada, 2014)
The development of advanced information technology has become a standard in the process of improving corporate value. This is seen through the high level of investors’ awareness of the brand and information that company holds (Da, Engleberg, and Gao, 2011; Bank, Larch, and George, 2011; Joseph, Wintoki, and Zhang, 2011). Among the information providers, internet plays an important role not only in accessing information, but also as a medium that can be applied to publish a wide range of financial reports or news to attract investors. This study aims to examine the effect of investors’ attention towards returns, liquidity and volatility of stock returns. The results indicate that investors’ attention which is represented by Google Insight contributes positively and significantly to the explanation of returns, liquidity, and volatility of stock returns in Indonesian manufacturing firms. Also, the phenomenon of information technology usage can be one of the considerations for investors in order to discover what types of company’s criterion that is appropriate to be included in their investment portfolio.